Quadriceps and hamstring muscle EMG activity during a football match - Kalema, Roudi (2012)
Roudi Kalema (2012). Quadriceps and hamstring muscle EMG activity during a football match. Department of Biology of Physical, University of Jyvaskyla. Master’s Thesis in Exercise Physiology. 58 pages. Fatigue represents a reduction in the ability of muscle to generate force and in the context of football, it has been often related with injury. Surface electromyography is a valuable technique for evaluating muscle activation and fatigue but it has never been applied during a football match. The development of washable textile electrodes has opened up possibilities to investigate muscular activity in non-laboratory settings, without skin preparation and wires hanging around the body. It has also been shown to be a valid and feasible method for assessing the average rectified value of electromyography (EMG). The aim of this study was to investigate the effect of football specific fatigue on EMG activity of right and left hamstring (RH, LH) and quadriceps (RQ, LQ) during an entire football match, using bursts analysis method. Muscle activity and inactivity were compared between the first 15 minutes of the 1st half (PRE) and last 15 minutes of the 2nd half (POST). Seven professional players (age 23.1 ± 3.13 years; height 181 ± 5.24 cm and mass 78.4 ± 10.5 kg) wore shorts with EMG electrodes during a match. EMG was normalized to maximal voluntary contraction (EMGMVC) and inactivity threshold was defined as an EMG level below 2% of EMGMVC. A low, moderate and vigorous activity threshold was determined during a 3 stages (1 minute) treadmill test. Low, moderate and vigorous threshold were defined as EMG value corresponding to the 3 running speeds (6 km/h, 12 km/h and16 km/h). Percentage of average normalized EMG (aEMGMVC,) decreased for RQ (- 27.2%), RH (- 29.6%) and LH (- 18.1%), (p<0.05). Burst analysis demonstrated a significant decrease in burst duration for RH (- 31.9%), LQ (- 22.8%) and an increase for LH (29.1%), (p<0.05). Burst amplitude significantly decreased for RQ (- 23.8%) and RH (- 20.2%), (p<0.05). Burst rate showed a significant decrease only for RQ (- 20%). Inactivity time significantly increased for LQ (+ 10.8%) and LH (+ 35.6%), (p<0.05). Low activity significantly increased for RQ (6.6%), (p<0.05). Moderate activity time decreased for RH (- 17.9%) and LH (- 23%), (p<0.05). Vigorous activity time was significantly reduced for RQ (- 31.3%), RH (- 37%) and LH (- 27.5%), (p<0.05). For the first time EMG was measured during an actual football match. It can be concluded that at the end of the match, EMG activity decreased, inactivity and low activity time increased while vigorous activity time decreased. These results suggest that a full 90 minutes football match reduces overall EMG activity. Further, at the end of the match EMG bursts were shorter and had a lower amplitude.